The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/mmr.2018.8937
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid enhances neointimal hyperplasia following vascular injury through modulating proliferation, autophagy, inflammation and oxidative stress

Abstract: Lysophosphatidic acid (LPA), which is one of the intermediate products of membrane phospholipid metabolism, is a bioactive phospholipid that possesses diverse activities. In the present study, the effects of LPA on neointimal formation following vascular injury were investigated. A carotid artery balloon injury model was employed in the present study, and following vascular injury, rats received an intraperitoneal injection of 1 mg/kg LPA. Subsequently, histopathological alterations were assessed by hematoxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…We found that this lipid by-product of autotaxin activity is involved in cancer, vascular defects, and neural tissue but is largely unexplored in the immune system. In blood vessels, LPA enhanced neo-intimal hyperplasia following vascular injury by modulating proliferation, autophagy, inflammation, and oxidative stress and may contribute to the pathology of atherosclerosis [37] whereas, in liver, can block the pathogenesis of acute liver injury decreasing inflammatory cytokines [38]. In glial cells through its receptor, LPA protects from oxidative stress [39] and exerts antiaging effect in age-related diseases by improving the anti-oxidative ability of yeast cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…We found that this lipid by-product of autotaxin activity is involved in cancer, vascular defects, and neural tissue but is largely unexplored in the immune system. In blood vessels, LPA enhanced neo-intimal hyperplasia following vascular injury by modulating proliferation, autophagy, inflammation, and oxidative stress and may contribute to the pathology of atherosclerosis [37] whereas, in liver, can block the pathogenesis of acute liver injury decreasing inflammatory cytokines [38]. In glial cells through its receptor, LPA protects from oxidative stress [39] and exerts antiaging effect in age-related diseases by improving the anti-oxidative ability of yeast cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…LPA, as a phospholipid signaling molecule, which is produced from circulating lysophosphatidylcholine (LPC) by ATX, is involved in multiple cardiovascular diseases ( Smyth et al, 2014 ; Chen et al, 2017 ; Gu et al, 2017 ; Nsaibia et al, 2017 ; Shen et al, 2018 ). It has been reported that LPA is present in abundance in the serum of patients with an acute myocardial infarction (AMI) ( Chen et al, 2003 ), and LPA1 and LPA3 receptor protein levels are increased in the ischemic heart that develops cardiac remodeling, implying that LPA plays a role in cardiac remodeling after a MI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that LPA inhibits autophagy in starvation-induced cancer cells ( Chang et al, 2007 ). Recently, LPA has been reported to promote neointimal hyperplasia after vascular injury by regulating autophagy ( Shen et al, 2018 ). In the present study, the results showed that LPA suppresses activation of autophagy in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The proliferation and migration of vascular smooth muscle cells (VSMCs) into the intima is the key pathological basis of AS. 2 In response to vascular injury, VSMCs undergo a phenotypic transition from a contractile (also termed differentiated) state to a synthetic (also termed dedifferentiated) state and subsequently maintain abnormal proliferation, migration, and matrix synthesis, contributing to AS. 3,4 Thus, therapeutic targeting aimed at promoting beneficial changes in VSMC phenotype may be a viable strategy of treating AS.…”
Section: Introductionmentioning
confidence: 99%